Vegetative and Environmental Components in a Secondary Riparian Forest in the Southern Plateau of Santa Catarina, Brazil - Lilian Iara Bet Stedille; Juliano Pereira Gomes; Newton Clóvis Freitas da Costa; Paula Iaschitzki Ferreira; Pedro Higuchi; Adelar Mantovani (Floresta e Ambiente, 2018)
ABSTRACT This study investigated the vegetation and environmental variable of fragments at different successional stages in a secondary riparian forest in the municipality of Ponte Alta, Santa Catarina state, Brazil (27°29’00” S and 50°17’11” W, WGS84), aiming to list priority variables for monitoring forest succession in riparian forests. For this, two areas were identified: “Reference” (conserved secondary forest) and “Restoration” (secondary forest under passive restoration). The Principal Component Analysis (PCA) indicated the existence of differences in the arboreal community diversity with lower values for the “Restoration” synthesized by PC1. The ground coverage by Ocellochloa rudis (Nees) Zuloaga & Morrone (Poaceae) was mainly in places with higher pH values and ability for effective cation exchange, with no preference of occurrence in either evaluated site. The composition of arboreal diversity was a relevant variable for monitoring passive restoration in this environment.